Students' acceptance of an educational videos platform: a study in a portuguese university - Costa, Carolina (2018)
The Educast is an  educational  videos’ platform that captures simultaneously video and digital support materials. This paper presents a study on the acceptance of Educast, by students, using the Technology Acceptance Model–TAM. The data was collected through a questionnaire applied to 54 students which results were analyzed using descriptive analysis and non-parametric tests. It was concluded that students expressed a positive attitude towards the variables Perceived Ease Of Use, Perceived Usefulness and Attitude Toward Using. The comparison between ratings assigned to the questionnaire items by the students who viewed video recordings and those that did not was performed, and it was found that the former showed higher levels of agreement with the referred items than the latter. It is considered that introducing some training before students have contact with Educast should be taken into account. The result of this work can be valuable not only for researchers on the Education area, but also for teachers that intend to use educational videos in their teaching/learning environment.